Qualitative radiographic characteristics of MRONJ-affected bone in oral and parenteral drug administration: comparison of panoramic radiography and cone-beam CT - Elif Aslan; Erinc Onem; Ali Mert; B. Guniz Baksi (BMC Oral Health)
Abstract Background Our aim was to compare the capacity of panoramic radiography (PR) and cone-beam computed tomography (CBCT) first for the detection of bone affected by medication-related osteonecrosis of the jaw (MRONJ) using qualitative radiographic parameters; and second for the evaluation of the relationship between drug administration route and associated bone changes. Methods PR and CBCT images of 24 MRONJ patients using oral or intravenous (IV) bisphosphonates were scored for the detection of osteolysis, osteosclerosis, lamina dura thickening, periodontal ligament widening, persistent extraction socket, sequestration, periosteal new bone formation, narrowing of the inferior alveolar canal, pathologic fracture, and cortical bone erosion. Fisher’s Exact and independent samples t-tests were used for comparisons (p = 0.05). Results The most frequent parameters observed in PR of all patients were osteosclerosis, osteolysis and cortical bone erosion, respectively. The equivalent rank in CBCT was cortical bone erosion, osteosclerosis and osteolysis. CBCT showed better diagnostic performance for the detection of periosteal new bone formation and cortical bone erosion in both oral and IV bisphosphonate groups (p < 0.05). No difference was obtained between the diagnostic performances of two imaging methods for the discrimination of the remaining parameters (p > 0.05). A higher number of radiographic markers were detected in both PR and CBCT images of patients using IV bisphosphonates (p > 0.05). Conclusion In this study, the diagnostic performance of PR was comparable to CBCT for the detection of most of the qualitative radiographic markers of MRONJ-affected bone in patients using oral and IV bisphosphonates. However, CBCT may be preferred for the diagnosis of periosteal new bone formation, cortical bone erosion, and pathologic fracture.